The Rare Benign Lesion That Mimics a Malignant Tumor in Breast Parenchyma: Nodular Fasciitis of the Breast - Hilal Erinanc; Emin Türk (Case Reports in Pathology)
We herein report the clinical and pathological findings of a rare case of nodular fasciitis in the breast parenchyma of a 48-year-old female. Because of potentially malignant findings on ultrasonography and during clinical examination, the patient underwent an excisional biopsy. Histologically, the lesion was composed of spindle to round shaped cells arranged in short bundles in a storiform pattern. Immunohistochemically, the cells were positive for vimentin and SMA and negative for desmin, S100, and CD34. Based on these morphological and immunohistochemical features, a diagnosis of nodular fasciitis was made. We emphasize that nodular fasciitis of the breast may show clinical features and imaging findings similar to those of breast cancer. The histopathologic diagnosis of nodular fasciitis can also be challenging. The purpose of this case report is to highlight the characteristics and the differential diagnosis of this rare neoplasm.